Penerapan Manajemen Riayah Dewan Kepengurusan Masjid dalam Meningkatkan Kenyamanan Jamaah Pada Masjid Agung As-Salam - Tunki Vurba; Purwandari, Elce; Artiyanto; Heru Prasetyo; Depi Putri (STAIN MAJENE, 2025)
This study aims to describe the implementation of riayah management (maintenance and care) in the preservation of the Grand Mosque As-Salam of Lubuklinggau City by the Mosque Prosperity Council (Dewan Kemakmuran Masjid or DKM). A qualitative descriptive method was employed, using data collection techniques such as observation, interviews, and documentation. The findings reveal that riayah management is implemented systematically by the DKM through well-defined task distribution, regular maintenance of the mosque building, and the provision of facilities that ensure the comfort of the congregants. The architectural style of the mosque reflects Middle Eastern influence, particularly through a dome inspired by the Nabawi Mosque, supported by 40 pillars symbolizing the age of Prophet Muhammad (PBUH) when he received the first revelation. Facilities include prayer halls, toilets, ablution areas, a library, a multimedia room, a secretariat office, a Quran Learning Center (TPA), and various supporting equipment such as Qur’ans, prayer garments, carpets, air conditioning units, and sound systems. The DKM conducts periodic renovations to maintain the building’s quality and ensure the functionality of the mosque's amenities. However, the study also identifies several challenges, including limited human resource development, poor adherence to standard operating procedures (SOPs), and technical disruptions. Despite these issues, the DKM remains committed to preserving the mosque’s role as a comfortable and welcoming place of worship and a center of Islamic activity. The study concludes that effective riayah management contributes significantly to maintaining a clean, orderly, and spiritually enriching environment for the community.